2007
DOI: 10.1021/jf071786o
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Killed Cells of Lactobacilli Skew the Immune Response Toward T Helper 1 Polarization in Mouse Splenocytes and Dendritic Cell-Treated T Cells

Abstract: It is believed that probiotics play an important role for the health of the host, including modulation of immune responses. Most studies have focused on the immunomodulatory effects of viable cells of lactic acid bacteria; however, we investigated those of heat-killed cells of lactic acid bacteria in this study. We first observed the effects on immune functions via stimulating splenocytes with three heat-killed Lactobacillus strains. Furthermore, we also investigated the effect of mouse dendritic cells (DCs) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 42 publications
1
61
0
1
Order By: Relevance
“…Furthermore, the heat-killed LAB, G-15 and SN13T, also exhibited the IgA-enhancing effect, suggesting that the result is consistent with those reported previously. 3,9,10) Interestingly, the supernatant fluids from LP28 and 15-1A cultures and the heat-killed LP28 and 15-1A cell mass were ineffective for enhancing IgA production. The heat-unstable substances such as proteins, which are contained in these LAB, might play a role in enhancing the IgA level produced by PPcells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the heat-killed LAB, G-15 and SN13T, also exhibited the IgA-enhancing effect, suggesting that the result is consistent with those reported previously. 3,9,10) Interestingly, the supernatant fluids from LP28 and 15-1A cultures and the heat-killed LP28 and 15-1A cell mass were ineffective for enhancing IgA production. The heat-unstable substances such as proteins, which are contained in these LAB, might play a role in enhancing the IgA level produced by PPcells.…”
Section: Discussionmentioning
confidence: 99%
“…Some substances as a cell wall component of LAB may function as immune stimulants in many cases, as shown in reports according to which heat-killed LAB are able to stimulate the immune response. 3,9,10) It has also been reported that the immunomodulatory activity of Bifidobacterium bifidum was not due to components secreted from bacteria. 5) Gram-positive bacteria, such as LAB, contain lipoteichoic acids as a component of the cell walls, which function as major immunostimulatory factors and agonists of the toll-like receptor 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of Li Xueping et al [16] showed that lactic acid bacteria can improve the production performance, intestinal health and immune function of broilers. The results of Chuang et al [17] Advances in Engineering Research,volume 129 showed that inactivation of lactic acid bacteria can stimulate cell proliferation and interleukin IL-10, IL-12 P70, interferon IFN-gamma production, and increase the secretion of T cell TH. Beatriz et al [18] showed that the expression of Osp A in lactobacillus plantarum promoted the secretion of cytokine IL-8 in intestinal epithelial cells, and the intestinal immune tolerance was broken by Th1/Th2 cell-mediated immunity.…”
Section: Immune Functionmentioning
confidence: 99%
“…It has been reported that some strains of probiotic lactobacilli can induce the production of several antiinflammatory and pro-inflammatory cytokines and other mediators of the immune response such as nitric oxide and reactive oxygen species [6][7][8]. Listeria monocytogenes is a Gram-positive food-borne pathogen that invades the intestinal epithelium, causing a potentially fatal disease, listeriosis.…”
Section: Introductionmentioning
confidence: 99%